Thinker tales an interactive play-based learning kit that explores the role of interest in fostering a positive attitude towards learning for preschool children age 3-5 - Millar, Daniela B.; San Valentin, Marc (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
Disengagement from learning is a problem any child faces. It starts off with the negative perception that surrounds learning. It is associated with work-an association that may be carried out through the years. When faced with the building social and academic pressures of big school, the children become overwhelmed, and consequently, unmotivated to learn. Positive learning experiences during preschool years are crucial if children are to persist, and not resist future learning. A common misconception is that only school is accountable for the children's learning and development. However, their own homes bear this responsibility, as well. This thesis aims to explore the home as an environment that can generate positive and meaningful learning experiences. I found that the home plays a powerful role in establishing a solid foundation for higher level learning, so we must make the most out of their time outside of school to instill a love of learning because it is from there that they may be motivated to learn well into their adulthood. As children, their learning revolves around play and interaction with other people and objects. Learning becomes enjoyable when the children are presented with opportunities for these. Enjoyable early encounters with learning positively affect the way children perceive learning, and how they perceive themselves as learners. In teaching children, their interests and tendencies are taken into consideration, so their motivation to learn becomes intrinsic. Keeping this in mind, this thesis seeks to create learning kit that will cater to the way children learn best-through play and interaction.
Thesis (Bachelor of Fine Arts major in Visual Communication)--University of the Philippines Diliman
Keywords: Learning